Field monitoring of sprinting power–force–velocity profile before, during and after hamstring injury: two case reports. Issue 6 (18th March 2016) - Mendiguchia, J.; Edouard, P.; Samozino, P.; Brughelli, M.; Cross, M.; Ross, A.; Gill, N.; Morin, J. B.
ABSTRACT: Very little is currently known about the effects of acute hamstring injury on over-ground sprinting mechanics. The aim of this research was to describe changes in power–force–velocity properties of sprinting in two injury case studies related to hamstring strain management: Case 1: during a repeated sprint task (10 sprints of 40 m) when an injury occurred (5th sprint) in a professional rugby player; and Case 2: prior to (8 days) and after (33 days) an acute hamstring injury in a professional soccer player. A sports radar system was used to measure instantaneous velocity–time data, from which individual mechanical profiles were derived using a recently validated method based on a macroscopic biomechanical model. Variables of interest included: maximum theoretical velocity ( V 0 ) and horizontal force ( F H0 ), slope of the force–velocity ( F – v ) relationship, maximal power, and split times over 5 and 20 m. For Case 1, during the injury sprint (sprint 5), there was a clear change in the F–v profile with a 14% greater value of F H0 (7.6–8.7 N/kg) and a 6% decrease in V 0 (10.1 to 9.5 m/s). For Case 2, at return to sport, the F–v profile clearly changed with a 20.5% lower value of F H0 (8.3 vs . 6.6 N/kg) and no change in V 0. The results suggest that the capability to produce horizontal force at low speed ( F H0 ) (i.e. first metres of the acceleration phase) is altered both before and after return to sport from a hamstring injury in these two elite athletes with little or no change of maximal velocity capabilities ( V 0 ), as evidenced in on-field conditions. Practitioners should consider regularly monitoring horizontal force production during sprint running both from a performance and injury prevention perspective.